Cycle‐Characteristic Odour of Cow Urine Can Be Detected by the Female Face Fly (Musca autumnalis). Issue 6 (22nd September 2014) - Nordéus, K; Webster, B; Söderquist, L; Båge, R; Glinwood, R
Contents Due to declining dairy cow fertility rates, there is great interest in developing tools for oestrus detection. Compounds in the volatile profile of oestrous cows are suggested as oestrus‐specific, but consistent results have not been presented. Certain haematophagous arthropods can discriminate stages of the mammalian reproductive cycle based on host volatiles. This study investigated whether the face fly, Musca autumnalis de Geer (Diptera: Muscidae), can discriminate between urine from cows in oestrus and urine collected during the luteal phase. Individual flies were tested in a two‐choice behavioural assay with choice between odour of oestrous or luteal urine and water (control). Flies chose the control arm significantly more when exposed to oestrous urine than when exposed to luteal urine. Analysis of volatiles showed that 1‐hexadecanol (cetyl alcohol) was released in greater amounts from oestrous urine than from urine collected during the luteal phase. In a dose response assay, flies were significantly attracted by 0.01 ng of 1‐hexadecanol but significantly repelled by 0.1 ng, a pattern consistent with fly responses to urine. In conclusion, M. autumnalis can discriminate between oestrous and luteal urine, and this may be mediated by differences in 1‐hexadecanol concentration.